2012
DOI: 10.1021/ja307315u
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Thiamin-Bound Intermediates and Microscopic Rate Constants for Their Interconversion on 1-Deoxy-d-xylulose 5-Phosphate Synthase: 600-Fold Rate Acceleration of Pyruvate Decarboxylation by d-Glyceraldehyde-3-phosphate.

Abstract: The thiamin diphosphate (ThDP)-dependent enzyme 1-deoxy-D-xylulose 5-phosphate (DXP) synthase carries out the condensation of pyruvate as 2-hydroxyethyl donor with D-glyceraldehyde-3-phosphate (D-GAP) as acceptor forming DXP. Toward understanding catalysis of this potential anti-infective drug target, we examined the pathway of the enzyme using steady state and pre-steady state kinetic methods. It was found that DXP synthase stabilizes the ThDP-bound pre-decarboxylation intermediate formed between ThDP and pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(178 citation statements)
references
References 26 publications
12
164
0
Order By: Relevance
“…42,43 The reaction commences with the typical ThDP-catalyzed pyruvate decarboxylation, and LThDP was found to be remarkably stable in the absence of d -GAP. 23 The principal results on DXPS are the following.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 The reaction commences with the typical ThDP-catalyzed pyruvate decarboxylation, and LThDP was found to be remarkably stable in the absence of d -GAP. 23 The principal results on DXPS are the following.…”
Section: Resultsmentioning
confidence: 99%
“…23 DXPS complexed with ThDP titrated with pyruvate (100–1000 µM) at 5 °C displayed a positive CD band at 312 nm, suggesting formation of the 1′,4′-iminopyrimidinylLThDP intermediate (Figure 10A). 23 These two CD bands were not apparent when apo-DXPS was complexed with MeOThDP (Figure 10B), indicating that MeOThDP has a different binding mode that does not give rise to the CD signatures for different forms of ThDP. Similar observations were made on the Arg478Ala variant of DXPS [for which an activity of 0.059 ± 0.007 µmol min −1 (mg of Arg478Ala DXPS) −1 was determined] (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay still involved an additional step for derivatization of the product. Recently, an assay based on circular dichroism has been reported for DXS (51). This assay appeared to be extremely important for studying the mechanistic behavior of DXS, illustrating detailed insights about different TPP-bound intermediates involved in the DXS-catalyzed reaction.…”
Section: Discussionmentioning
confidence: 99%
“…CD experiments, complemented with the TH method to assist the CD assignments, revealed that formation of LThDP is rate-limiting overall in the sequence of reactions carried out by DXPS [63,64]. However, LThDP is remarkably stable on the enzyme until the acceptor D-GAP is added.…”
Section: The Covalent Substrate-mentioning
confidence: 99%